(untitled) (Web of Teachers: Inderscience Research, 2024)
Avascular osteonecrosis of the femoral head (AVNFH) is an ischemic condition which despite different treatments often leads to collapse of the femoral head and to total hip arthroplasty. However, the magnetic resonance imaging findings predisposing to disease progression and total hip arthroplasty are somewhat elusive.To evaluate the magnetic resonance imaging findings of AVNFH and to assess the patterns of findings which may predict total hip arthroplasty. A retrospective study was conducted with a total of 18 diagnosed AVNFH treated with core decompression combined with intraosseous stem cell treatment. After treatment, magnetic resonance imaging followups were done at three-month and one-year follow-up or until total hip arthroplasty. Association Research Circulation Osseous classification and magnetic resonance imaging findings such as the size and the location of the AVNFH, bone marrow edema in femoral neck, effusion and subchondral fracture were evaluated. Hips advancing to total hip arthroplasty have more often bone marrow edema in femoral neck (90% vs. 0%), adjacent to necrotic lesion (100% vs. 43%) and in acetabulum (90% vs. 14%), but also subchondral fractures (70% vs. 0%), effusion (80% vs. 29%), and synovitis (80% vs. 14,3%). The greater size and the lateral weight-bearing location of the necrotic lesion also predicted future total hip arthroplasty. Hips advancing to total hip arthroplasty have often a combination of pathognomonic AVNFH imaging findings compared to hips not advancing to total hip arthroplast